Comparative Analysis of Cloud Deployment Models: Public, Private, Hybrid, and Multi-Cloud (International Journal of Engineering and Computer Science, 2025)
This article presents a comprehensive examination of cloud deployment models. The topic is timely because enterprises must navigate an increasingly complex cloud landscape to achieve competitive advantage. The study compares public, private, hybrid, and multi-cloud deployment models on the basis of current scholarly literature and industry data published between 2021 and 2025, with emphasis on their characteristics, benefits, limitations, and use cases. The research novelty lies in the systematic consolidation and analysis of recent studies on cloud-computing deployment, highlighting emerging trends and challenges in multi-cloud environments and their implications for strategic decision-making. The findings are relevant to IT executives, cloud-solution architects, information-technology researchers, and decision-makers engaged in digital transformation. They are also valuable to chief digital officers and chief financial officers who must assess risk and budgetary considerations when migrating infrastructure to the cloud. The principal conclusion is that no single deployment model is universally optimal; selection depends on an organization’s specific requirements for security, regulatory compliance, performance, cost, and control. A sustained shift toward hybrid and multi-cloud strategies is observed as organizations seek a balanced approach